Assessment of National External Quality Assurance Program of Pakistan (NEQAPP) as a tool for improving quality of lab results among participating laboratories - Shah, Shahrukh; Muhammad Aamir; Zujaja Haroon; Usman Munir; Afshan Bibi; Syed Raza jaffer (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the impact of the National External Quality Assessment Programme of Pakistan in improving the quality of laboratory results among the participating laboratories. Method: The cross-sectional observational study was conducted from July to December 2020 at the Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, in association with the National Quality Assurance Programme of Pakistan. A survey questionnaire was developed and sent to the participating laboratories via email. Frequencies of their responses were calculated and data was analysed using SPSS 21. Results: Of the 150 laboratories approached, 145(96.6%) responded. Among them, 140 (96.6%) laboratories were satisfied by the information provided on the programme’s portal, 123(84.8%s) were pleased with the responsiveness of the programme manager, 140(96.6%) reported quality of services had improved after participation in the programme, 129(89%) indicated that the clinician’s confidence had enhanced, and 122(84%) said the participation in the programme had improved the credibility of their respective of laboratories. Conclusion: The National External Quality Assessment Programme of Pakistan was found to have significantly contributed in improving the quality of laboratory results among the participating laboratories.